Efecto del Etilclozate sobre el desarrollo y tamaño final del fruto en el Albaricoquero - Agusti, M.=700 1 Juan, M.; Almela, V.; Speronoi, C.
(Es, En)
ilus.,13 ref.
Keywords: ALBARICOQUE; ESTERES; ANATOMIA DE LA PLANTA; DIMENSION; FRUTO; ESPAÑA; ETILCLOZATE